EVALUASI PELAKSANAAN KURIKULUM 2013 DI SEKOLAH DASAR MUHAMMADIYAH 09 PLUS JAKARTA TIMUR - Muslimah H. Bahrun; Betti Nuraini; Ihsana El Khuluqo (LPPM UNIVERSITAS BINA INSAN, 2021)
This research aims to the express an evaluation of the Implementation of Curriculum 2013 by using qualitative methods and the CIPP model (Context, Input, Process, Product) model: A Qualitative Study on Elementary School Muhammadiyah 09 Plus East Jakarta.The method used is Evaluation Research Method, that is a method which written statement, oral information and various facts to obtain data which relates to the problem of evaluation toward the implementations of Curriculum 2013. Data collection used documentation, interviews, and observation. Interviews were conducted at five Muhammadiyah Elementary School Pricincipals, curriculum Staffs, Infrastructure Staff and Classroom teachers. Research result concludes that in terms of context, the implementation of Curriculum 2013 in Elementary School Muhammadiyah 09 Plus is clear in its vision, mission and objective. But in tern of input, the implementation of curriculum 2013 is not controlled well yet. It is seen from the input of teachers and employes who did not graduate from PGSD but from one field of study. The process implementation of curriculum 2013 is running well, it is in accordance with the procedures established by the government curriculum. There products in the implementation of Curriculum 2013 in Elementary School Muhammadiyah 09 Plus both in academic was good.